Exploring Developing Economies: Emerging Local Economies and Displaced Urbanisation: The Case of KwaMhlanga - Shibambu, Nhlalala (University of the Witwatersrand, Johannesburg, 2024)
This research explores the economic evolution of KwaMhlanga, a settlement in Mpumalanga province, within the context of debates over displaced urbanism—a concept that describes how people living in areas that were developed under Apartheid's forced relocations, which are far from urban centres and densely populated, are developing informal economies to sustain themselves (Mosiane and Gotz, 2021). The study investigates whether KwaMhlanga represents a form of displaced urbanism and examines its potential to function as a viable economic node. It builds on Mosiane and Gotz’s (2021) framework, which characterizes displaced urbanism as communities developing informal economies and modern infrastructure despite historical displacements. The research evaluates KwaMhlanga's economic potential by analysing policy, infrastructure, land use regulations, and the roles of local institutions, traditional authorities, and small businesses. The research methods that were used were semi-structured interviews with the Ndebele Traditional Authority and Thembisile Hani Local Municipal Official and business owners located along the R573. Observations using Google Earth were made of the KwaMhlanga crossroads and the businesses located there, these observations were mapped. Findings suggest that while KwaMhlanga is evolving economically in a limited way, with some growth of small scale businesses and the development of a mall, challenges such as inadequate services and weak institutional support hinder its development as a functional economic node. The study’s limitations include the inability to interview formal businesses at the KwaMhlanga Shopping Complex and limited sample size due to businesses unwillingness to be interviewed.
A research report submitted in fulfillment of the requirements for the Masters in Development Planning , In the Faculty of Engineering and the Built Environment , School of Architecture and Planning, University of the Witwatersrand, Johannesburg, 2024
Keywords: UCTD; Displaced Urbanisation; Local Economies; Developing Economies; SDG-8: Decent work and economic growth